The architecture of coopetition: strategic intent, ambidextrous managers, and knowledge sharing - Seepana, Chandrasekararao; Paulraj, Antony; Huq, Fahian Anisul (2020)
The study investigates the significance of strategic intent, manager's ambidexterity, and knowledge sharing routines for firms in their quest to pursue coopetition. We utilize the resource-based view and the dynamic capabilities theory to ground our hypotheses. We test the hypotheses using the data collected from 313 firms that engage in coopetition relationships through an online survey. The findings forward knowledge sharing and ambidextrous managers as intervening variables, in that when complemented with knowledge sharing, a firm's strategic intent could better guide the firm's managers to pursue coopetition successfully. Findings further advocate that knowledge sharing complements to enable the relationship between a firm's strategic intent and its ambidextrous managers, as well as the relationship between strategic intent and coopetition. Furthermore, results also indicate that ambidextrous managers, with a skillset of a combination of exploration and exploitation, are positively associated to coopetition. Overall, the findings make important theoretical as well as empirical contributions to the coopetition and strategic alliance literature.